PENGARUH NON PERFORMING FINANCING TERHADAP LIKUIDITAS BANK MUAMALAT - Mukhlisul Muzahid; Hamdani Hamdani; Khairil Fata; Salma K Nisa (Politeknik Negeri Lhokseumawe, 2026)
This study examines the impact of Non Performing Financing (NPF) from Murabahah, Mudharabah, and Musyarakah contracts on the liquidity of Bank Muamalat Indonesia during 2016-2024. Using multiple linear regression analysis, the study found that Murabahah and Musyarakah NPFs individually do not significantly affect the bank's liquidity. However, Mudharabah NPF shows a positive and significant influence on liquidity, indicating the bank's ability to reallocate funds from problematic financing to more liquid assets. Nevertheless, collectively, all three types of NPF simultaneously have a significant impact on Bank Muamalat Indonesia's liquidity, emphasizing the importance of comprehensive risk management to maintain the financial stability of Islamic banks..Keywords: NPF, Murabahah, Mudharabah, Musyarakah, Liquidity